Strategic Housing Policy, Migration and Sorting around Population Thresholds - Kristof De Witte; Benny Geys (Center for Economic Studies and ifo Institute (CESifo), 2015)
We analyse whether, when and how local office-holders respond to the personal, economic incentives embedded in exogenously imposed population thresholds leading to an increased number and/or remuneration of local office-holders. Using data from all 589 Belgian municipalities over the period 1977-2014, local politicians are found to purposefully influence population growth through policy measures aimed at stimulating net in-migration when approaching important population thresholds. We provide evidence that strategic housing policy decisions – i.e. granting additional building permits early in the election cycle to maximize population growth just before the `deadline' to surpass a population threshold – act as a key mechanism.
Keywords: H70; J18; R23; R38; 330; rent-seeking; political agency; regression discontinuity designs; building permits